Nutritional aspects in the sportsman's functional rehabilitation program - Fondi A; D'Angelo A; Bartoletti A; Di Giacinto G; Ripari P (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2023)
The adoption of a proper dietary regimen is of vital importance in the sports practice of athletes, as it is able to ensure an adequate turn-over of all those substances that are consumed with exercise. Our purpose was to demonstrate how adequate protein intake can favorably influence the post-injury rehabilitation phase. Our work is presented as a case-control study on a group of 16 competitive athletes recovering from sports injuries who were prescribed a balanced diet with, to 8 of them, oral supplementation with a pool of amino acids in optimal composition in the dose of 1g/kg/day. In the two groups, recovery time, muscle strength, and injured limb diameter were taken as variables. It was observed that the group treated with amino acid supplementation had statistically significant benefits compared with the group treated with diet prescription alone.